NRG1/ERBB Axis in Drug Tolerance to Targeted Cancer Therapies - Peltola, Sara (My University, 2024)
Targeted therapies have benefited many patients, but resistance significantly hinders the long-term efficacy of these treatments. Development of resistance is complex and can occur through various mechanisms including involvement of drug-tolerant persister cells. These nonproliferating cells can survive under drug exposure by nongenetic mechanisms and, over time, acquire mutations that confer therapy resistance. The erythroblastic leukemia viral oncogene homolog (ERBB) receptor family including epidermal growth factor receptor (EGFR), ERBB2, ERBB3 and ERBB4 is linked to many cancers. Exogenous neuregulin 1 (NRG1), a ligand of ERBB3 and ERBB4, strongly promotes resistance to targeted therapy in oncogene-addicted cancer cell lines. Additionally, previous data from our group show an upregulation of NRGs and their receptors in drug-tolerant cells. The main goal of this thesis was to determine the functional relevance of upregulation of NRGs and their receptors in drug-tolerant cells. The first aim was to investigate whether the upregulation of NRGs and their receptors result in elevated activation of the ERBB receptors, which was analyzed by western blotting in five cancer cell lines treated with targeted therapies for up to 30 days. The second aim was to study the necessity of ERBB receptors to the drug-tolerant cells by CRISPR-Cas9-mediated knockout. The most prominent reactivation of the ERBB signaling was observed in ALK-rearranged adenocarcinoma and BRAF-mutated colorectal cancer cell lines H3122 and HT-29, respectively. The knockout studies further implicate the importance of EGFR, ERBB2 and ERBB3 to drug-tolerant H3122 cells and ERBB2 to drug-tolerant HT-29 cells. In future studies it would be meaningful to investigate whether blocking of these receptors by an antibody upon the original targeted therapy treatment decreases cancer cell viability, which would suggest the potential of the treatment combination in the clinic.
Keywords: cancer, drug-tolerant persister cells, ERBB receptor, NRG